Pertanggungjawaban Pidana Korporasi terhadap Tindak Pidana yang Dilakukan oleh Karyawan Marketing - Mohamad Ulin Nuha (Jurnal Cakrawala Hukum, 2018)
This study aims to resolve legal problems that occur related to promotions that mislead consumers and commit fraud against money received from consumers. However, in the criminal justice process only sales are held to be held personally accountable, not corporations who are held accountable. This study examines the legal position of corporations in the criminal justice system in Indonesia, then how to determine corporate errors and criminal liability of corporations in criminal acts of consumer protection. In order to answer this problem, reviewing Court decisions using Law Number 8 of 1999 concerning Consumer Protection is accompanied by theories of corporate criminal liability. Corporations have been recognized as the subject of criminal law in the criminal justice system in Indonesia and if corporate members who commit crimes have a working relationship with the corporation, the crimes committed by corporate members are still within the scope of their work, as well as providing benefits to the corporation. Corporations can be held liable if the authority given to its members is misused. Corporations can be asked for criminal responsibility if the work culture or corporate work system is considered too loose so that it is used by its members to commit crimes. The form of corporate criminal liability is in the form of principal penalties in the form of fines and additional crimes in the form of compensation to consumers.How to cite item: Nuha, M. (2018). Pertanggungjawaban Pidana Korporasi terhadap Tindak Pidana yang Dilakukan oleh Karyawan Marketing. Jurnal Cakrawala Hukum, 9(1), 99-106. doi:https://doi.org/10.26905/idjch.v9i1.2192